Unraveling Internal Conflicts in East Asia and the Pacific: Incidence, Consequences, and Resolution - Bercovitch, Jacob; DeRouen, Karl (Lexington Books, 2011)
Civil wars and internal conflicts pose the greatest threat to international peace and security in the twenty-first century. Nowhere is this problem more acute than in East Asia and the Pacific, which has far more of its share of such conflicts. Unraveling Internal Conflicts in East Asia and the Pacific: Incidence, Consequences, and Resolution, edited by Jacob Bercovitch and Karl DeRouen, Jr., is a book of originally commissioned essays on civil wars which provide a compelling area of inquiry. Many of the Asia-Pacific region's wars are very long (such as in Myanmar), some tend to recur (also in Myanmar); some involve religion (Philippines, Thailand), and some (Aceh, Bougainville, East Timor) of the longest have ended in the last few years. In short, the region presents a variety of interesting dynamics that merit close attention in one volume.